Stylistic dominants of poetical cycle “Amoretti” by E. Spencer (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
This article analyzes the main stylistic devices in the sonnets of E. Spencer “Amoretti”. It was determined that his poetry is characterized by a broad system of stylistic devices: Phonostylistic (alliteration, anaphora, epiphora, metaplasm) syntactic shapes, paths (metaphors, epithets, personification, metonymy, antonomasia, hyperbole, litotes, oxymoron, comparison). The author also uses allusions, symbols, and allegories. It was demonstrated that the style of E. Spencer suggests he was a master with a special sense of poetic form, organically stylistic devices, the brightness of language constructs.
Keywords: Edmund Spenser; Elizabethans; sonnet cycle; “Amoretti”; phonostylistic funds; stylistic figures; trails